Professor John Pollard: Half-Century of Australian Neurology - Tam, Johnny; Holm-Mercer, Leah (Advances in Clinical Neuroscience & Rehabilitation, 2020)
With a career in medicine and academia spanning over five decades, Professor John Pollard has devoted much of his life to the development of Australian neurology. His fascinating career has been punctuated with numerous achievements, particularly in the field of inflammatory neuropathies. Now at the age of 79, he continues to work as an active Consultant Neurologist and Co-Director at Sydney’s Brain and Mind Centre, seeing and treating patients. In May 2019 we caught up with Professor Pollard after a busy afternoon list of clinic.